1998
DOI: 10.1161/01.cir.97.16.1557
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assessment of Significant Left Anterior Descending Coronary Artery Stenosis by Coronary Flow Velocity Reserve With Transthoracic Color Doppler Echocardiography

Abstract: CFVR determined by TTDE is useful in the noninvasive assessment of significant stenotic lesion in the LAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
259
4
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(277 citation statements)
references
References 39 publications
10
259
4
4
Order By: Relevance
“…CFR is the difference between the basal, autoregulated coronary flow and the maximal flow, at any given perfusion pressure,19, 20 but it is calculated as the ratio between hyperemic and resting coronary flow. To date, CFR can be easily assessed by transthoracic Doppler echocardiography by recording Doppler‐derived flow velocities with great feasibility on the mid‐distal left anterior descending artery (LAD) 21. CFR of LAD has shown excellent compliance with invasive Doppler flow wire and optimal reproducibility 22, 23.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CFR is the difference between the basal, autoregulated coronary flow and the maximal flow, at any given perfusion pressure,19, 20 but it is calculated as the ratio between hyperemic and resting coronary flow. To date, CFR can be easily assessed by transthoracic Doppler echocardiography by recording Doppler‐derived flow velocities with great feasibility on the mid‐distal left anterior descending artery (LAD) 21. CFR of LAD has shown excellent compliance with invasive Doppler flow wire and optimal reproducibility 22, 23.…”
Section: Introductionmentioning
confidence: 99%
“…CFR of LAD has shown excellent compliance with invasive Doppler flow wire and optimal reproducibility 22, 23. Several conditions can be associated with decreased CFR, such as a significant epicardial coronary artery stenosis, but also aging, aortic valve stenosis, left ventricular (LV) hypertrophy, hypertrophic and dilated cardiomyopathy, and even isolated coronary microvascular dysfunction 20, 21, 22, 23. Although previous studies have shown an inverse relationship between arterial stiffness and CFR,24, 25 limited information is available on the relationships between PP and CFR, in particular in patients who have cardiovascular risk factors but are free of obstructive coronary artery disease 26, 27, 28.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a decrease in the release of endothelium-derived nitric oxide has been well documented in experimental animal models of hypertension as well as in hypertensive patients (23). Recently, we reported a significant correlation between CFVR, forearm endothelial function and asymmetric dimethylarginine, which is an endogenous (14,16).…”
Section: Discussionmentioning
confidence: 71%
“…CFVR was defined as the ratio of hyperemic to basal MDV. We adopted a CFVR of less than 2.0 as the cut-off value for the presence of significant coronary arterial stenosis, as has been done in published reports (14,16).…”
Section: Cfvr Measurement Using Transthoracic Doppler Echocardiographymentioning
confidence: 99%
“…It is also influenced by serious epicardial coronary stenosis, previous myocardial infarction, etc. Pharmacological hyperemic vasodilatation induced by adenosine is a reliable and reproducible technique with which CFVR is evaluated by Doppler echocardiography (3,10). Adenosine is often used to assess microcirculatory function on the basis of their ability to induce maximal vasodilatation of coronary resistance vessels.…”
mentioning
confidence: 99%